RANCANGAN BANGUN SISTEM INFORMASI PEMESANAN DAN PENJADWALAN TOUR GUIDE BERBASIS WEBSITE DENGAN ALGORITMA FIRST-COME-FIRST-SERVED - Maulana Ihsan; Yulia Fatmi; Yeka Hendriyani; Resmidarni Resmidarni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The purpose of this study is to design and develop a web-based information system for booking and scheduling Tour guide services that can effectively, efficiently, and systematically facilitate the online reservation process for tourists. The system uses the First-Come-First-Served (FCFS) algorithm to automatically manage the order of bookings and scheduling of Tour guides. It is also designed to present clear and transparent information regarding Tour guide service fees across several tourist destinations in Pesisir Selatan. The system development method used is the prototype method. This method enables direct interaction between developers and users during the development process, allowing system requirements to be understood more clearly and reducing the risk of specification errors. The prototype method applied consists of several main stages: communication, quick planning, modeling quick design, construction of prototype, and deployment and feedback. The results of this study show that the developed system is able to significantly improve the quality of tourism services. The system successfully integrates information on tourist destinations, tour guide services, and the booking process into a single platform that is easily accessible, interactive, and well-structured, thereby helping tourists plan their trips more effectively.